Skeletal Muscle Vascular Control During Exercise: Impact of Nitrite Infusion During Nitric Oxide Synthase Inhibition in Healthy Rats. (March 2016) - Ferguson, Scott K.; Glean, Angela A.; Holdsworth, Clark T.; Wright, Jennifer L.; Fees, Alex J.; Colburn, Trenton D.; Stabler, Thomas; Allen, Jason D.; Jones, Andrew M.; Musch, Timothy I.; Poole, David C.
The nitric oxide synthase (NOS)-independent pathway of nitric oxide (NO) production in which nitrite (NO2 − ) is reduced to NO may have therapeutic applications for those with cardiovascular diseases in which the NOS pathway is downregulated. We tested the hypothesis that NO2 − infusion would reduce mean arterial pressure (MAP) and increase skeletal muscle blood flow (BF) and vascular conductance (VC) during exercise in the face of NOS blockade via L-NAME. Following infusion of L-NAME (10 mg kg −1, L-NAME), male Sprague-Dawley rats (3-6 months, n = 8) exercised without N G -nitro-L arginine methyl ester (L-NAME) and after infusion of sodium NO2 − (7 mg kg −1 ; L-NAME + NO2 − ). MAP and hindlimb skeletal muscle BF (radiolabeled microsphere infusions) were measured during submaximal treadmill running (20 m min −1, 5% grade). Across group comparisons were made with a published control data set (n = 11). Relative to L-NAME, NO2 − infusion significantly reduced MAP ( P < 0.03). The lower MAP in L-NAME+NO2 − was not different from healthy control animals (control: 137 ± 3 L-NAME: 157 ± 7, L-NAME + NO2 − : 136 ± 5 mm Hg). Also, NO2 − infusion significantly increased VC when compared to L-NAME ( P < 0.03), ultimately negating any significant differences from control animals (control: 0.78 ± 0.05, L-NAME: 0.57 ± 0.03, L-NAME + NO2 − ; 0.69 ± 0.04 mL min −1 100 g −1 mm Hg −1 ) with no apparent fiber-type preferential effect. Overall, hindlimb BF was decreased significantly by L-NAME; however, in L-NAME + NO2 −, BF improved to a level not significantly different from healthy controls (control: 108 ± 8, L-NAME: 88 ± 3, L-NAME + NO2 − : 94 ± 6 mL min −1 100 g −1, P = 0.38 L-NAME vs L-NAME + NO2 − ). Individuals with diseases that impair NOS activity, and thus vascular function, may benefit from a NO2 − -based therapy in which NO bioavailability is elevated in an NOS-independent manner.